An occupational justice perspective on playing football and living with mental distress. Issue 1 (2nd January 2021) - Pettican, Anna; Speed, Ewen; Kilbride, Cherry; Bryant, Wendy; Beresford, Peter
ABSTRACT: Physical inactivity is a global public health priority, yet people living with a disability or long-term health condition, such as those who experience mental distress, continue to face inequalities and barriers to participation in sport and physical activity. These inequalities are considered an occupational injustice, in terms of participation in health enhancing occupations being restricted for these groups of people, despite them wanting to be more active. This study aimed to gain an in-depth understanding of the nature and value of participating in a UK based community football project, for people with experience of mental distress. Twenty-three people took part in this first strand of a larger participatory action research study, which used the World Café as a method for structuring and recording conversations. Data from the three World Café events were analysed collectively and thematically. The study's findings reveal tensions, nuances, and subtleties that exist in relation to the reciprocal relationship between playing football and people's health and well-being. The complexity of enabling participation in sport and physical activity amongst marginalised groups, such as people with experience of mental distress, is highlighted.